Aesthetics of atabs in the novels of Hamid al-Uqabi - Muhammed Kadhim, Asma; Abbas Darwish, Khudhair (Al-Adab Journal, 2020)
Aesthetics in narrative work is not limited to form only, or content only, but is achieved by meeting them together and becomes work. A great effort rests with the novelist in order to achieve aesthetics. Not every text can achieve this. This procedure is highly dependent on the culture of the novelist, and his skill in formulating his text through his mastery of writing tools, in addition to his wide imagination, which leads him to suggest different methods than what It is common in writing, and the formulation of accurate Addresses for its texts. These Addresses did not reach the goal of encouraging and attracting the reader, rather they were consistent and a function of the content and idea of the novel, and this gave it aesthetic that adds to the aesthetic of the Addresses itself.